Parametric Study of the SUR Method for the Simulation of Quasi-Brittle Materials (The International Journal of Engineering & Information Technology (IJEIT), 2024)
In this paper, the authors study the influence theform of the smooth unloading-reloading function on thenonlinear solution characteristics of the recently developedsmooth unloading-reloading (SUR) approach for nonlinearfinite element simulation of quasi-brittle materials. TheSUR method uses a target function and a smooth unloadingreloadingfunction to compute an approximate tangentmatrix with an incremental-iterative Newtown type solutionscheme. The smooth unloading-reloading function has twomain parameters p a and ν which affect the form of the SURfunction. The study is illustrated using different values ofthe two main parameters of the SUR curve. A Mathcad codehas been written to carry out the nonlinear finite elementanalysis of the numerical example presented in this paper.